IDIOMS AND PROVERBS IN THE ENGLISH LANGUAGE (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article explores the expression of idioms and proverbs which constitute an important part of the lexical and cultural wealth of any language. They reflect the traditions, values, and worldview of a particular community. The English language contains a vast number of idiomatic expressions and proverbs that are widely used in everyday communication, literature, and media. The purpose of this article is to analyze the linguistic nature of idioms and proverbs in English, their semantic features, structural characteristics, and cultural significance. The study also highlights their communicative and expressive functions and discusses their role in language learning and intercultural communication.